RETROSPECTIVE ANALYSIS OF SOCIAL RESPONSIBILITY IN RUSSIA - Elena V. Smirnova; Svetlana V. Mitrofanova (Вестник Северо-Кавказского федерального университета)
The article is devoted to the development of social responsibility in Russia in different periods of history. The experience of solving social problems of the society in dorevolitsionny, Soviet, the modern period of Russian history.